Is There Room for Individual Patient-Specified Preferences in the Patient-Reported Outcome Measurement Revolution? - Leif I. Solberg; Jeanette Y. Ziegenfuss; Rachael L. Rivard; Christine K. Norton; Robin R. Whitebird; Glyn Elwyn; Mark Swiontkowski (Journal of Patient-Centered Research and Reviews, 2023)
Purpose: The study aim was to test the feasibility of collecting qualitative patient-preferred outcomes or goals and the degree of their attainment as an addition to a standardized process for collecting quantitative composite patient-reported outcome measures (PROMs) from patients undergoing knee joint replacement..